2008
DOI: 10.1038/hdy.2008.70
|View full text |Cite
|
Sign up to set email alerts
|

H1 tau haplotype-related genomic variation at 17q21.3 as an Asian heritage of the European Gypsy population

Abstract: In this study, we examine the frequency of a 900 kb inversion at 17q21.3 in the Gypsy and Caucasian populations of Hungary, which may reflect the Asian origin of Gypsy populations. Of the two haplotypes (H1 and H2), H2 is thought to be exclusively of Caucasian origin, and its occurrence in other racial groups is likely to reflect admixture. In our sample, the H1 haplotype was significantly more frequent in the Gypsy population (89.8 vs 75.5%, Po0.001) and was in Hardy-Weinberg disequilibrium (P ¼ 0.017). The 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A genome-wide association (GWA) study for sporadic PD cases in Europe confirmed that MAPT is closely linked to sporadic PD ( 26 ). MAPT is divided into two haplogroups called H1 and H2 based on whether the gene is in the inverted orientation ( 27 ). A meta-analysis in Caucasian populations reported that the H2 haplotype is more relevant to PD than the H1 haplotype, as the risk of suffering from PD is lower in Caucasians with the H2 haplotype ( 28 ).…”
Section: Assembled Tau In Pdmentioning
confidence: 99%
“…A genome-wide association (GWA) study for sporadic PD cases in Europe confirmed that MAPT is closely linked to sporadic PD ( 26 ). MAPT is divided into two haplogroups called H1 and H2 based on whether the gene is in the inverted orientation ( 27 ). A meta-analysis in Caucasian populations reported that the H2 haplotype is more relevant to PD than the H1 haplotype, as the risk of suffering from PD is lower in Caucasians with the H2 haplotype ( 28 ).…”
Section: Assembled Tau In Pdmentioning
confidence: 99%
“…Tau protein is encoded by a single gene comprising 16 exons [105, 106]. Exons 2, 3, and 10 undergo alternative splicing; however, exon 3 is expressed only in the presence of exon 2, thus yielding 6 isoforms.…”
Section: Vesicle Trafficking Dysfunctionmentioning
confidence: 99%
“…There are two common haplotypes spanning the entire MAPT coding region ensued from an ancestral inversion of 900 kb on chromosome 17q21: the directly oriented H1 and the inverted H2 [ 56 ]. Whereas the H1 haplotype is common in all populations, the H2 haplotype is thought to be exclusively present in populations of Caucasian origin, rare in Africans and nearly absent in Americans and East Asians [ 57 ]. Data from GWAS studies and meta-analyses supported the common MAPT H1 haplotype as a susceptibility factor for sporadic PD with an OR of approximately 1.5 [ 49 , 58 , 59 , 60 ].…”
Section: The Genetic Landscape Of Parkinson’s Disease: a Brief Overviewmentioning
confidence: 99%